Uji Kalibrasi Alat Ukur Massa pada Neraca Analitik Menggunakan Metode Perbandingan Langsung - Fitri Rahmah; Fathiyah Fairuz Salsabila (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
The research describes the effect of weights on the calibration results of an analytical balance. This study aims to obtain the uncertainty value of the analytical balance test results by comparison with the standard E2 class weights. The study results can be used to determine the feasibility of the measuring instrument tested through the analysis of the performance value of the scales based on the Limit of Performance (LOP) parameter. The method used is a direct comparison method with E2 class weights. The calibration process carried out in this method includes the measurement of repeatability of readings, deviations from the nominal value indication, the effect of loading not at the centre of the pan, and hysteresis. The data analysis includes standard deviation values, minimum correction values, hysteresis, uncertainty, and LOP. The calibration results show that the reading power of the standard deviation of the load at ½ maximum capacity and full maximum capacity is 0.0042 grams. Deviations at measuring points 20, 40, 60, 80, 100, 120, 140, 160, 180, and 200 grams have a maximum correction value of 0.04995 grams with a maximum measurement uncertainty of 0.006378585 grams and a value of k=2.0 at 95% confidence level. In the performance table of the scales based on the LOP value, it is known that the performance of the scales is in the poor category, and it is more advisable to repair the tool.